A review of the ion exchange leaching method for extracting rare earth elements from ion adsorption clay - Nurul Aniyyah, Mohamad Sobri; Noorlisa, Harun; Mohd Yusri, Mohd Yunus (Elsevier Ltd, 2024)
As the demand for REEs rises, ion adsorption clay emerges as a promising alternative REE source. Ion exchange leaching is the most effective way for REE extraction since 90% of the total REEs exists in an ion exchangeable phase. Recent research focused on enhancing REE leaching efficiency through leaching experiments to identify optimal leaching solutions and conditions. This review aims to summarize the findings from various studies examining the factors that influence REE leaching efficiencies. These factors include the type and concentration of leaching solution, pH, temperature, leaching time, flow rate, liquid-to-solid ratio, and particle size of the clay. This study also provides an overview of mathematical modelling methods utilized to describe the leaching process, including Fick's law, the Kerr model, the Shrinking Core model, Darcy's law, and the Van Deemter equation. The paper highlights the process of determining the rate determining step among these models, deriving the rate constant based on three leaching parameters (solution concentration, temperature, and clay particle size), and presenting the final equation of the Shrinking Core model. These insights will offer valuable guidance on leaching conditions before conducting actual experiments, presenting a more efficient and cost-effective methodology.